(3bWGQ GdCTHGMs ((3GdLjRI, eUQs (3fgVI eUQs, 2014)
(3eGPG jMOK YfOeG JYhj GdPFGH hJWjQ GdNaGajT hjShO GdXdGe aj eOjfI GdQYH? EfgG eLQO djdI QheGfSjI CNQi fbQC ajgG GdeRjO ef GdbUU GdQGFYI hGdeQYHI deZGeQGJ ejcj hcfOT eY GdCTQGQ GdeNjajf hcja jecfgG GdJZdH Ydjge, dcf GfJHghG aNda GdCHhGH GdeZdbI jhLO GdcKjQ ef GdCehQ GdeNjaI GdJj JKjQ GdQYH aj GdbdhH hCjVG GdVMcGJ JYGdhG eYG dfONd gPG GdYGde GdQGFY eQI CNQi aj gPG GdYOO GdLOjOs
(3GdNjhd GdOhGQI (B-- (3CfJ JSCd hcfOT jLjH (B-- (3gd gPG Mbjjbj (B-- (3SQ GdbfGY (B-- (3GdcGHhS (B-- (3GdhMT GdeQJLa (B-- (3CTHGM aj cd ecGf (B-- (3gOjI YjO GdejdGO (B-- (3eG hQGA GdSJGQ (B-- (3edc GdNOGY (B-- (3JMJ VhA GdbeQs
(3bUU eUhQIs
1 5 6 11 12 13 16 18 21
Keywords: (3GdbUU GdeUhQIs